Analysis of quality control criteria in an business with the fuzzy DEMATEL method: Glass business example - Celik, Mirac Tuba; Arslankaya, Seher (Academic Publication Council, 2023)
Quality is at the forefront of the issues to which the production and service sectors attach importance. Increasing customer satisfaction, gaining competitive advantage in the industry, increase in sales vb. for many reasons, companies have increased the importance given to quality control. Before sending the products to the customer, taking into account the necessary quality control criteria, the control of the products will contribute to the solution of any problems that may arise in advance. Especially in sectors where energy and capital are intense, and the capacity is very high, it is one of the fundamental processes that should be done in the company, inspection of products taking into account all quality control criteria. Therefore, it is essential to consider the glass industry in this sense. This study determines the critical value of the quality control criteria on the glass, which a company that produces tempered glass pays attention to before putting the product used as a contract into production. Control criteria were determined by interviewing a team of experts in the company, and then the criteria were evaluated by experts. Then, fuzzy DEMATEL method, which is one of the multi-criteria deci-sion-making techniques, was used and the relations of the criteria with each other were determined. As a result of the calculations made with fuzzy DEMATEL, the criteria are listed as K1 > K2 > K4 > K7 > K6 > K5 > K3 and the aspect measurement with a criterion weight of 0,150 was found to have the most significant effect on the glass.
Keywords: Fuzzy DEMATEL; Glass industry; Multi -criteria decision making; Quality control